Comparative study of maximum isometric grip strength in different sports - Noé Gomes Borges Junior; Susana Cristina Domenech; Jonathan Ache Dias; Affonso Celso Kulevicz da Silva; Yoshimasa Sagawa Junior (Universidade Federal de Santa Catarina, 2009)
The objective of this study was to compare maximum isometric grip strength (Fmax)between different sports and between the dominant (FmaxD) and non-dominant (FmaxND) hand. Twenty-nine male aikido (AI), jiujitsu (JJ), judo (JU) and rowing (RO) athletes and 21non-athletes (NA) participated in the study. The hand strength test consisted of maintainingmaximum isometric grip strength for 10 seconds using a hand dynamometer. The position of the subjects was that suggested by the American Society of Hand Therapy. Factorial 2X5 ANOVA with Bonferroni correction, followed by a paired t test and Tukey test, was used for statistical analysis. The highest Fmax values were observed for the JJ group when using the dominant hand,followed by the JU, RO, AI and NA groups. Variation in Fmax could be attributed to handdominance (30.9%), sports modality (39.9%) and the interaction between hand dominance andsport (21.3%). The present results demonstrated significant differences in Fmax between the JJ and AI groups and between the JJ and NA groups for both the dominant and non-dominant hand. Significant differences in Fmax between the dominant and non-dominant hand were only observed in the AI and NA groups. The results indicate that Fmax can be used for comparisonbetween different sports modalities, and to identify differences between the dominant and nondominanthand. Studies involving a larger number of subjects will permit the identification of differences between other modalities.